148k views
3 votes
Solve for x(2x+3)(3x-2)=(3x+3)(2x-2)

User Jessecurry
by
4.3k points

1 Answer

6 votes

To solve for x, we need to apply distributive property as:


\begin{gathered} \left(2x+3\right)\left(3x-2\right)=\left(3x+3\right)\left(2x-2\right)​ \\ 2x\cdot3x+2x\cdot(-2)+3\cdot3x+3\cdot(-2)=3x\cdot2x+3x(-2)+3\cdot2x+3\cdot(-2) \\ 6x^2-4x+9x-6=6x^2-6x+6x-6 \\ 6x^2+5x-6=6x^2-6 \\ 6x^2+5x-6+6=6x^2-6+6 \\ 6x^2+5x=6x^2 \\ 6x^2+5x-6x^2=6x^2-6x^2 \\ 5x=0 \\ x=0 \end{gathered}

Answer: x = 0

User Shashwat Gupta
by
5.2k points